Hubungan Dukungan Keluarga dan Kualitas Hidup pada Pasien Diabetes Melitus di Rumah Sakit Santa Elisabeth Medan - Ance M. Siallagan; Rotua Elvina Pakpahan; Friska Sembiring; Lisa Suwaty Simanjuntak (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Diabetes mellitus is the second leading cause of death worldwide after cardiovascular disease. This condition causes physical and psychological burdens. Quality of life is influenced by various aspects, including the ongoing special needs of diabetes mellitus patients. Family support is a form of assistance provided by family members to provide physical and psychological comfort when someone is ill. This study aims to determine the relationship between family support and quality of life of diabetes mellitus patients at Santa Elisabeth Hospital Medan in 2024. This type of research is quantitative with a correlational design and a cross-sectional approach. The sampling technique used purposive sampling with a sample size of 80 respondents. Inclusion criteria included patients who had been diagnosed with diabetes mellitus for more than one year, were accompanied by their family, and were able to communicate in Indonesian. Data collection was conducted using the HDFSS questionnaire and the DQOL questionnaire. The results showed high family support and a high quality of life for diabetes mellitus patients. The Spearman statistical test produced a p-value of 0.048 and a correlation of 0.222. Thus, there is a positive relationship between family support and quality of life for diabetes mellitus patients. This means that the higher the family support, the better the patient's quality of life. Based on the results of this study, hospitals are advised to provide education regarding the importance of family support in influencing the quality of life of diabetes mellitus patients.